BRAND IMAGE EXPLORATION IN ENSURING CUSTOMER SATISFACTION IN THE TODAY'S COFFEE SHOP BUSINESS - Muh. Husriadi; Maulidia Berlianti; Triwulandari Nehru Putri (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Contemporary coffee shops face challenges in maintaining customer loyalty and satisfaction despite offering similar products. Likewise, understanding the role of brand image in shaping customer satisfaction is still limited. This study aims to explore in depth the role of brand image, product quality, service, atmosphere and digital media in ensuring customer satisfaction in contemporary coffee shops in Kendari city. The research method used is descriptive qualitative with data collection through in-depth interviews and direct observation of customers and selected coffee shop managers. The results of the study indicate that a strong and consistent brand image supported by product quality, friendly service, comfortable atmosphere and creative digital communication have an effect on customer satisfaction and loyalty. The implications of this study emphasize the importance of integrated branding strategies and active customer involvement to increase the competitiveness of contemporary coffee shops in a competitive market.